DOI: 10.4018/978-1-4666-6094-6.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Computer Interfaces for Assessment and Communication in Disorders of Consciousness

Abstract: Many patients with Disorders of Consciousness (DOC) are misdiagnosed for a variety of reasons. These patients typically cannot communicate. Because such patients are not provided with the needed tools, one of their basic human needs remains unsatisfied, leaving them truly locked in to their bodies. This chapter first reviews current methods and problems of diagnoses and assistive technology for communication, supporting the view that advances in both respects are needed for patients with DOC. The authors also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 102 publications
0
18
0
1
Order By: Relevance
“…A recent review showed that 4 of 24 patients (17%) who had been diagnosed as being in a vegetative state were not only consciously aware but could answer yes or no questions 20 . BCIs offer a method to evaluate awareness and to restore a communication channel.…”
Section: Communicationmentioning
confidence: 99%
“…A recent review showed that 4 of 24 patients (17%) who had been diagnosed as being in a vegetative state were not only consciously aware but could answer yes or no questions 20 . BCIs offer a method to evaluate awareness and to restore a communication channel.…”
Section: Communicationmentioning
confidence: 99%
“…A recent review showed that 4 of 24 patients (17%) identified as being in a vegetative state were not only consciously aware but could answer yes or no questions [161]. Other potentially communicative patients with disorders of consciousness might be undetectable through standard clinical testing, but may benefit from BCI.…”
Section: Future Bci Directionsmentioning
confidence: 99%
“…These included presentations on auditory-, tactile- and motor imagery-based BCI paradigms from the DECODER project [121, 161163] and the usage of auditory- and motor imagery-based BCIs for communication with people who have disorders of consciousness [164, 165]. The results of 3 clinical studies on BCI and disorders of consciousness were presented [166–170].…”
Section: Future Bci Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to communication and control applications, BCI technology can also be used for the assessment of cognitive functions of patients with disorders of consciousness (DOC) or locked-in syndrome (LIS) [1,2,3]; (Ortner et al, in press). The top-right corner of Fig.…”
Section: Introductionmentioning
confidence: 99%